2012
DOI: 10.3184/174751912x13371679868473
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles Solid Phase Acidic Catalyst for One-Pot Synthesis of Octahydroquinazolinone Derivatives

Abstract: The reaction between dimedone, an aromatic aldehyde and urea catalysed by ZnO nanoparticles (ZnO NPs) in refluxing ethanol as a solvent provided a simple and efficient one-pot route for the synthesis of octahydroquinazolinone derivatives in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In continution of our investigations of the application of solid acids in organic synthesis [5][6][7][8][9][10][11] we have found that the Hantzsch synthesis of 1,4-dihydropyridine derivatives by the threecomponent condensation of an aromatic aldehyde 1, a 1,3-dicarbonyl compound such as ethyl acetoacetate 2, or indane-1,3-dione 3 and ammonium acetate occurs very rapidly and smoothly in the presence of 0.003 g nano-BF 3 .SiO 2 as a catalyst (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In continution of our investigations of the application of solid acids in organic synthesis [5][6][7][8][9][10][11] we have found that the Hantzsch synthesis of 1,4-dihydropyridine derivatives by the threecomponent condensation of an aromatic aldehyde 1, a 1,3-dicarbonyl compound such as ethyl acetoacetate 2, or indane-1,3-dione 3 and ammonium acetate occurs very rapidly and smoothly in the presence of 0.003 g nano-BF 3 .SiO 2 as a catalyst (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of previous research on the use of solid acids in organic synthesis [12][13][14][15][16] , we have investigated the synthesis of biscoumarin derivatives by the condensation of 4-hydroxycoumarin 1 and an aromatic aldehyde 2 or phenylglyoxal 3 in the presence of 0.008g HClO 4 -SiO 2 NPs catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, several catalysts and reagents have been reported for the synthesis tetrahydroquinazolinones, such as Nafion‐H, [ 38 ] PEG‐HClO 4, [ 39 ] TMSCl, [ 40 ] ceric ammonium nitrate (CAN), [ 23 ] ZnO NPs, [ 41 ] CuI NPs, [ 42 ] [bmim] + BF 4 − and [bmim] + Br −,[ 43 ] Cu@Ag Core‐Shell nanoparticle, [ 44 ] indium (III) trifluoromethane sulfonate In (OTf) 3, [ 28 ] MoO 3 ‐ZrO 2 nanocomposite oxide, [ 45 ] molybdenum anchored onto zeolite beta (Mo@imine‐Z), [ 46 ] SiO 2 ‐NaHSO 4, [ 47 ] ZrOCl 2 .8H 2 O, [ 48 ] acidic ionic liquid [Tbmim]Cl 2 /AlCl 3, [ 49 ] Cu/SiO 2, [ 50 ] CNT–Fe 3 O 4 –PTh nanocomposite, [ 51 ] phosphotungstic acid nanoclusters grafted onto high surface area hydrous zirconia PWA/ZrO 2, [ 52 ] Ytterium iron garnet supermagnetic Y 3 Fe 5 O 12 (YIG), [ 24 ] (Me (Im) 12 )H 4 CuPW 11 O 39 as a surfactant type, [ 53 ] Zn (OTf) 2, [ 54 ] and p ‐Toluenesulfonic acid. [ 55 ] However, many of these methods suffer some drawbacks such as high‐temperature reaction, long reaction times, poor yields, and use of hazardous or costly catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] In recent decades, because of the versatility of the reaction and the vast growth applications of the end-products, such as tetrahydroquinazolinones and dihydropyrimidinone (DHPMs), the Biginelli reaction has gained high ranking as one of the most popular multicomponent reactions (MCRs) in the synthesis of heterocyclic compounds. [26,27,[29][30][31] In literature, several catalysts and reagents have been reported for the synthesis tetrahydroquinazolinones, such as Nafion-H, [38] PEG-HClO 4, [39] TMSCl, [40] ceric ammonium nitrate (CAN), [23] ZnO NPs, [41] CuI NPs, [42] [bmim] + BF 4 À and [bmim] + Br À, [43] Cu@Ag Core-Shell nanoparticle, [44] indium (III) trifluoromethane sulfonate In (OTf) 3, [28] MoO 3 -ZrO 2 nanocomposite oxide, [45] molybdenum anchored onto zeolite beta (Mo@imine-Z), [46] SiO 2 -NaHSO 4, [47] ZrOCl 2 .8H 2 O, [48] acidic ionic 2…”
Section: Introductionmentioning
confidence: 99%